Impact of wear and diet on molar row geometry and topography in the house mouse. (September 2017) - Renaud, Sabrina; Ledevin, Ronan
Highlights: Tooth geometry and topography vary with age-related wear within species. Soft food eaters display more worn teeth, less helical tooth rows and lower relief for the upper molar row. Tooth complexity may be relevant in wild populations as it is insensitive to age. Comparing upper and lower molar relief may reveal differences in food consistency. Abstract: Objectives: Dental evolution affects the geometry of the tooth, but the adaptive relevance of these changes is related to tooth sharpness, complexity, and relief (topography). On a set of laboratory mice, we assessed how wear related to age and food consistency affected molar geometry and topography. Design: Three groups of laboratory inbred mice (C57BL/6J strain) were considered: Four week old mice close to weaning, six month old mice fed on regular rodent pellets, and six month old mice fed on rodent pellets that were powdered and served as jelly. Their upper and lower molar rows were imaged in 3D. The geometry of the surfaces was quantified using a template describing the whole surface of the rows. Topographic indices were estimated on the same surfaces. Results: The geometry of the molar rows was heavily affected by age-related wear. Food consistency affected mostly the upper molar row, which was more worn and less helical in soft food eaters. Tooth sharpness and relief decreased with age-related wear. Tooth relief was lower in soft food eaters, but only on the upper molar row. Tooth complexity was insensitive to wear. Conclusion: The primary factor affecting tooth geometry and topography is age-related wear, as wear erodes the molar surfaces. Tooth complexity, however, appears to be insensitive to wear, making this index relevant for comparison of tooth morphology among wild mice of unknown age. Soft food eaters displayed more worn teeth, with less helical molar row occlusal surface, possibly because behavior and jaw morphology were disturbed due to this unusual food resource.